Trillin protects against doxorubicin-induced cardiotoxicity through regulating Nrf2/HO-1 signaling pathway - Xinyi Yang; Sili Liu; Miyan Liu; Didong Lou; Wenjun Zou; Xiaofen Li (PLoS ONE, 2025)
Doxorubicin (DOX) is widely employed in anticancer therapy, but its clinical application is constrained by its cardiotoxic effects. Trillin, a bioactive compound derived from Trillium tschonoskii Maxim., has been identified as a natural antioxidant possessing cardioprotective properties. This study aimed to ascertain whether trillin can protect against DOX-induced cardiotoxicity (DIC) through its inherent antioxidant capabilities. In vivo studies, C57BL/6 mice were administered DOX (5 mg/kg i.p.) via intraperitoneal injection once weekly for a total of five consecutive weeks and received trillin (25, 50 and 100 mg/kg i.g.) through intragastric administration once daily for six weeks. In vitro studies, H9c2 cardiomyocytes were utilized to verify the protective efficacy of trillin (0.5, 1 and 2 μM) against DIC. Trillin significantly mitigated DOX-induced myocardial damage, which encompassed improvements in left ventricular function, reductions in serum cardiac enzymes levels, and diminution of heart cell vacuolation. Moreover, trillin effectively attenuated DIC while preserving the anticancer efficacy of DOX. Trillin also alleviated oxidative injury by elevating levels of SOD and GSH and reducing MDA levels. Additionally, trillin restored the expression of Nrf2 and HO-1 in mouse hearts and H9c2 cardiomyocytes treated with DOX. Trillin safeguarded against DIC by inhibiting oxidative stress via upregulation of the Nrf2/HO-1 pathway. These findings furnish evidence suggesting trillin may serve as a therapeutic agent for the prevention of DIC.